Meta-Analisis Tentang Perilaku Koping Prevenstif dan Stres - Ahmad Muhammad Diponegoro; Syamsul Bachri Thalib (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2001)
This meta-analysis study focused on preventive coping and stress. Individual's study don't shows the result that not always consistent and sometimes contradict each other. So, it is difficult to get the inclusive and integrative conclusion.The purpose of this study is to integrate the results of the study that varied about the relation between preventive coping and stres throughmeta-analysis procedure. The subject analysis contained 15 studies that consist 2816 sample size. The result of this study reveals that (a) there is a relation between preventive coping and stres (rho= -0,383, interval confidence 95% = -0,02 <P < 0,74); (b) variance due to sampling error=0,0043 (15,09%); (c) variance due to variation of reliability= 0,0012 (4. 18%). This meta-analysis support concfution in the current literatur. The relation between preventive coping and stress became consis tence 1f we consider the research artifact. either the amount of the sample, subject characteristics of research instruments. Key words: meta-anausls. penlaku koping preventif, dan sires